ORGANOLEPTIC AND TVB ASSESSMENTS ON COMMON CRAP (Cyprinus carpio)WITH DIFFERENT MORTALITY PROCESSES DURING STORAGE AT ROOM TEMPERATURE - Siregar, Riri Andriani; Karnila, Rahman; Sukmiwati, Mery (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This research intended to determine changes in organoleptic and TVB values of common crap (Cyprinus carpio) by different mortality processes during storage at room temperature. The treatment given consisted of P1 (died picker inMedullaoblongata) and P2 (death floundered). The analysis parameters observed were organoleptic value (eyes, gills, and odors ) and TVB content.The assessments were conducted every 2 hours for 14 hours of storage. From the research results,the best treatment was P1. Organoleptic in P1 and P2 respectively were eye 4.5, 3.3, gills 4.1, 3.3, odor 4.2, 2.9. Furthermore, TVB P1 at 0 hours of observation had the best value of 2.39 mgN/100g and reached the quality rejection limit at 14 hours of the observation, 30.33 mgN/100g. TVB P2 at 0 hours of observationhad a value of 6.45 mgN/100g and reached the quality rejection limit at 12 hours of the observation, 30.33 mgN/100g. Keywords:common crap, death floundered ,Medulla oblongata, mortality process, Organoleptic, TVB.